In vivo Models of HIV Disease and Control - Friedman, Herman; Specter, Steven; Bendinelli, Mauro; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
An AIDS vaccine is still elusive and HIV treatment continues to develop multidrug resistance at alarming rates. Because of the similarities between HIV and immune deficiency infections in a variety of animals, it is only natural that scientists use these animals as models to study pathogenesis, treatment, vaccine development and many other aspects of HIV. Part of the series Infectious Agents and Pathogenesis, this volume reviews the immune deficiency virus in a variety of hosts. Pathogenesis, vaccine and drug development, epidemiology, and the natural history of the monkey, mouse, cat, cow, horse, and other animal viruses are detailed and compared to HIV. Also included are chapters on the history and future of animal models, as well as a chapter on ethical and safety considerations in using animal models for AIDS studies.
Historical Perspective -- Animal Model Systems of HIV-Diseases -- Chemokines and Their Receptors and the Neuropathogenesis of HIV-1 Infection -- SCID Mice Transplanted With Human Cells as Small Animal Models in AIDS Research -- SIV as a Model for AIDS Pathogenesis Studies -- SIV Infection of Macaques as a Model for AIDS Drug Studies -- FIV as a Model for HIV: An Overview -- FIV as a Model for AIDS Pathogenesis Studies -- Drugs of Abuse, AIDS, and the FIV Model -- FIV as a Model for AIDS Vaccine Studies -- FIV as a Model for HIV Treatment -- Equine Infectious Anemia Virus as a Model for Lentiviral Pathogenesis -- Studies of the Structure of Caprine Arthritis-Encephalitis Virus Surface Envelope Glycoprotein -- Ethical Issues in the Use of Animal Models of Infection and Some Practical Refinements -- Future Perspectives.
Keywords: Infectious diseases; Allergy; Microbiology; Immunology; Infectious Diseases; Allergology; Microbiology; Immunology